HST and UKIRT imaging observations of z ~ 1 6C radio galaxies - I. The data - Inskip, K; Best, P; Longair, MS; Rawlings, S; Rottgering, H; Eales, S (2003)
The results of Hubble Space Telescope and UKIRT imaging observations are presented for a sample of 11 6C radio galaxies with redshifts 0.85 < z < 1.5. The observations of the 6C sources reveal a variety of different features, similar to those observed around the higher luminosity of the aligned emission appears less extreme in the case of the 6C radio galaxies. For both samples, the aligned emission clearly cannot be explained by a single emission mechanism; line emission and related nebular continuum emission, however, often provide a significant contribution to the aligned emission.